Local Folktale-Based Digital Literacy Media for Strengthening Reading and Writing Skills of Fifth-Grade Elementary Students - Cerianing Putri Pratiwi; Heny Kusuma Widyaningrum; Nico Irawan (Jurnal Pemberdayaan Masyarakat, 2026)
Reading and writing are basic skills that students must master. This study aims to describe the needs for literacy media, develop digital literacy media containing local folktales, and test its effectiveness in improving students' reading and writing skills. This study uses the Research and Development method with the ADDIE model (analysis, design, development, implementation, and evaluation). Data were collected through observation, interviews, questionnaires, and tests. The analysis indicates the need for media that is engaging and aligned with students' characteristics. The developed media was deemed valid by content experts, feasible by media experts, and received very positive responses from teachers and students. The effectiveness test showed a significant difference between the experimental and control groups. The experimental group's average score was higher than the control group's. These findings indicate that digital media containing local folklore are effective in improving students' reading and writing skills and contribute to learning grounded in local wisdom.